The importance of administrative data in the evaluation of the incidence of social housing allowance programmes - Raya, Josep Maria; Torres-Pruñonosa, Jose (Elsevier, 2022)
The aim of this work is to assess the rental assistance programme that was implemented by the Catalan regional government in the 2010s using administrative data provided by the Catalonia Housing Agency to analyse whether it achieved its aims to enhance the design of similar programmes. Linear probability models to explain the probability of receiving the grant were estimated and some significant variables were identified: age; rent price; expertise; being a woman; non-EU citizenship and the number of old, young or disabled members. Multiple regressions were estimated in regard to the grant’s rate in relation to the rent price and the effort required to pay relative to income after having received the grant. The results suggest that rental assistance facilitates access to housing to groups that face more difficulties and that the revenue captured by landlords, although statistically significant, is small, since they capture approximately 3% by raising prices. This aid, despite being controlled by different variables, benefits elderly people more than young people, which must be addressed because, theoretically, when access requirements are met, no group should benefit more than others.
Keywords: rental assistance; allowance; housing; rent subsidies; administrative data; social governmental programme; Scopus; JCR